Spin relaxation in antiferromagnetic Fe–Fe dimers slowed down by anisotropic DyIII ions - Mereacre, Valeriu; Klöwer, Frederik; Lan, Yanhua; Clérac, Rodolphe; Wolny, Juliusz A.; Schünemann, Volker; Anson, Christopher E.; Powell, Annie K. (Beilstein Journal of Nanotechnology, 2013)
By using Mössbauer spectroscopy in combination with susceptibility measurements it was possible to identify the supertransferred hyperfine field through the oxygen bridges between DyIII and FeIII in a Fe4Dy2 coordination cluster. The presence of the dysprosium ions provides enough magnetic anisotropy to “block” the hyperfine field that is experienced by the iron nuclei. This has resulted in magnetic spectra with internal hyperfine fields of the iron nuclei of about 23 T. The set of data permitted us to conclude that the direction of the anisotropy in lanthanide nanosize molecular clusters is associated with the single ion and crystal field contributions and 57Fe Mössbauer spectroscopy may be informative with regard to the the anisotropy not only of the studied isotope, but also of elements interacting with this isotope.
Keywords: anisotropy; dysprosium; iron; Mössbauer spectroscopy